The Prevalence of High Carcinogenic Risk of HPV Genotypes among HIV-Positive and HIV-Negative MSM from Russia. (2nd June 2021) - Beliakov, Ilia; Senina, Maria; Tyulenev, Yuriy; Novoselova, Elena; Surovtsev, Viktor; Guschin, Alexander
Abstract : Objective . Men who have sex with men (MSM) have a high risk of lifelong anal cancer caused by high-risk human papillomavirus (HR HPV) infections. The aim of this study was to investigate the prevalence of anal canal HR HPV infection among men who have sex with men (MSM) with and without HIV infection in Moscow (Russia). We evaluated associations of some HIV coinfections (HSV and CMV) and HPV distribution among MSM with and without HIV infection. Methods . Two groups of HIV-positive ( n = 60) and HIV-negative ( n = 60) MSM were evaluated in the study. Fourteen high-risk (HR) HPV types, HSV1/2, and CMV were investigated in men anal swabs. Results . HR HPVs were found with nearly the same frequency of 66.7% in both groups: HIV-positive and HIV-negative MSM. HIV-positive status was statistically associated with the presence of several (more than two) HPV types (p = 0.044 ). The most prevalent HR HPV genotypes were HPV18, HPV16, HPV56, and HPV33 for HIV-positive MSM and HPV56, HPV51, HPV66, and HPV16 for HIV-negatives. We found a statistically significant association of five HR HPV types with HIV status of MSM: HPV16 (p = 0.028 ), HPV18 (p = 0.00006 ), HPV58 (p = 0.003 ), HPV33 (p = 0.019 ), and HPV39 (p = 0.026 ). The frequency of HSV1 (1.7%) and HSV2 (10%) infections and CMV (3.3%) infection was evaluated in the group of HIV-positive MSM. The frequency of HSV1 (5%) and HSV2 (6.7%) infections and CMV (0%) infection was evaluated, as well, in the group of HIV-negative MSM. Conclusion . Multiple HPV genotypes were detected significantly more often than single HPV genotype in the group of HIV-positive MSM. According to our data, 25% of HIV-positive MSM have HPV39; this is the only one of the five types of HR HPV (16, 18, 58, 33, and 39) associated with this group of MSM that has not yet been included in the HPV vaccines available on the market.